Baseline reduction algorithm for direct absorption spectroscopy with interference features. (11th December 2019) - Wang, Zhenhai; Fu, Pengfei; Chao, Xing
Abstract: A baseline reduction algorithm for determining gas temperature and concentration from absorption spectra with interfering features using direct absorption spectroscopy is proposed. Empirical baselines are obtained through non-absorbing baseline transform, and background subtraction is done by reducing the first three components of the orthogonal polynomial expansion of the measured spectra. The algorithm is first validated by numerical simulation using the absorption lines of CO ( R (9) and R (17)) located between 2179 and 2180 cm −1, which provides a correct estimation of temperature and CO concentration. Then the method is demonstrated in premixed CH4 /air flat flame. The temperature is determined with a precision of 20 K, and the detection limit for CO is 400 ppm at 1835 K with 4.70% CO and 4.70% CO2 interference. Both the simulation and experimental results show that the algorithm is well suited for interpreting absorption spectra with neighbouring interference features as are often encountered in practical combustion environments.